The effects of sprint running traning on sloping surfaces - Paradisis, G. P.; Cooke, C. B. (The Journal of Strength and Conditioning Research, 2006)
The aim of this study was to examine the effects of sprint running training on sloping surfaces (3°) on selected kinematic and physiological variables. Thirty-five sport and physical education students were randomized into 4 training groups (uphill-downhill, downhill, uphill, and horizontal) and a control group, with 7 participants in each group. Pre- and posttraining tests were performed to examine the effects of 6 weeks of training on the maximum running speed at 35 m, step rate, step length, step time, contact time, eccentric and concentric phase of contact time, flight time, selected posture characteristics of the step cycle, and peak anaerobic power performance. Maximum running speed and step rate were increased significantly (p < 0.05) in a 35-m running test after training by 0.29 m/s (3.5%) and 0.14 Hz (3.4%) for the combined uphill-downhill group and by 0.09 m[middle dot]s-1 (1.1%) and 0.03 Hz (2.4%) for the downhill group, whereas flight time shortened only for the combined uphill-downhill training group by 6 milliseconds (4.3%). There were no significant changes in the horizontal and control groups. Overall, the posture characteristics and the peak anaerobic power performance did not change with training. It can be suggested that the novel combined uphill-downhill training method is significantly more effective in improving the maximum running velocity at 35 m and the associated horizontal kinematic characteristics of sprint running than the other training methods are.